Establishing the Median and 95% Effective Doses of Oliceridine for Immediate Post-Surgical Analgesia Following Laparoscopic Cholecystectomy: A Double-Blind, Sequential Dose-Finding Study - Cao, Xianghua; Xiao, Huiling; Yan, Haoran; Wei, Yujiao; Wen, Qiting; Zhang, Zhijian; Xu, Guizhen; Xu, Binbin; Chen, Jian; Li, Xueping (Drug design, development and therapy, 2025)
This investigation aimed to establish the optimal dosing parameters of oliceridine for postoperative pain control in laparoscopic cholecystectomy (LC) procedures. Using Dixon and Massey's up-and-down sequential allocation method, the median effective dose (ED50) and the dose required for 95% effective dose (ED95) were determined, alongside an evaluation of the agent's safety profile. In this prospective trial, 82 participants scheduled for LC were enrolled and randomly assigned to receive either oliceridine or saline (control). Prior to surgical incision, the intervention group received varying doses of intravenous oliceridine, while control subjects received equivalent volumes of saline solution. Post-surgical pain management involved standardized multimodal analgesic protocols for both cohorts. Baseline demographic data was documented for all participants. Pain evaluations using the 11-point verbal numeric rating scale (NRS) at 15 min, 30 min, and 2h post-extubation. Using Dixon's up-and-down methodology, the ED50 and ED95 were determined. Hemodynamic variables were tracked and pain levels quantified throughout the procedure. The study protocol included monitoring post-anesthetic recovery characteristics and documenting adverse effects. Probability unit regression analysis indicated that the ED50 of oliceridine for the prevention of early postoperative pain was calculated to be 18.45 µg/kg (95% CI: 16.85-19.82 µg/kg), while the ED95 was determined to be 22.39 µg/kg (95% CI: 20.75-26.98 µg/kg). Statistical analysis showed comparable rates of adverse events between study groups (p > 0.05). Additional analyses demonstrated similar outcomes between oliceridine and control cohorts regarding hemodynamic stability, and adverse effect profiles. Pain management satisfaction assessment at 24 hours post-LC revealed high approval rates in the oliceridine group, with 90% of patients (36/40, p=0.31) and 97.5% of surgeons (39/40, p=0.03) expressing satisfaction, regardless of administered dose. Our findings establish that for early postoperative pain management, oliceridine demonstrates optimal therapeutic efficacy at an ED50 of 18.45 ug/kg, with the ED95 determined to be 22.39 ug/kg.